First description of calling song of Arcyptera alzonai and possible taxonomic implications (Insecta: Orthoptera, Acrididae, Gomphocerinae) - Anselmo, Luca (Fragmenta entomologica, 2020)
The aim of this study was to contribute to the knowledge of Arcyptera alzonai, considered an endemic Italian species, whose biology is little known and which has an uncertain taxonomic status. Some individuals were found on a small site within its historical presence area in Susa Valley (Piedmont, NW Italy). Some recordings of the song, until today unknown, were made and analyzed. From the oscillograms obtained, no significant differences emerged with the congener species Arcyptera microptera. Also according to various authors these two species are at the moment indistinguishable from a morphological point of view. Therefore, a possible synonymy among these two taxa can be assumed which, however, must be investigated and confirmed by further research based on genetic analysis.